Digitalizing Islamic Education: Developing a Methodological Model for Generation Z Learners - Humaida Humaida; Intan Kurnia Wati; Mukmin Mukmin; Shakila Kausar (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2026)
Generation Z, as digital natives, experiences significant transformations in how they access, interpret, and engage with Islamic knowledge within rapidly evolving digital environments. This shift creates an urgent need to reformulate Islamic studies methodologies to align with their learning characteristics and digital behaviours. This study aims to explore the conceptual foundations, methodological orientations, and practical strategies for developing a Digital Islamic Studies framework relevant to Generation Z. This research employs a library research design and a content analysis approach, examining scholarly literature on Islamic education, digital culture, and Generation Z learning patterns. Data were collected through documentation and analysed using thematic categorisation and interpretative synthesis. The findings reveal that digital platforms such as TikTok, Instagram, and YouTube function as primary epistemic spaces for Generation Z, reshaping religious authority, learning preferences, and modes of value internalisation. However, significant challenges remain, including misinformation, limited educator digital competence, a lack of structured digital literacy frameworks, and algorithm-driven biases. The study also highlights the need to integrate interactive, multimodal, and collaborative learning approaches to enhance engagement and comprehension. This research implies that Islamic studies must adopt an adaptive, interdisciplinary, and digitally integrated methodology to remain relevant in the contemporary era. Strengthening religious digital literacy and developing platform-aware pedagogical strategies are essential to ensure the accuracy, integrity, and meaningful transmission of Islamic knowledge among Generation Z.